Impact of Backsheet Variety on Inverter Availability - Buerhop-Lutz, Claudia; Stroyuk, Oleksandr; Hauch, Jens; Peters, Ian Marius (IEEE Journal of Photovoltaics, 2024)
Recent studies show that the choice of backsheets and encapsulants can be essential for the operational readiness of inverters, which affects system revenue. A key module property determined by the backsheet is ground impedance, which needs to exceed a threshold value or the inverter fails to connect to the grid - it trips. We studied the impact of different backsheets on insulation resistance and inverter trippings by evaluating the time series of ground impedance values measured by the inverters. We identified the composition of 29 118 backsheets in the field using near-infrared spectroscopy. We sorted backsheets into three major classes: polyamide (PA), polyethylene terephthalate-based multilayer backsheets with a fluorinated coating (FC), and 'others' comprising less frequently used, similarly behaving backsheets. Then, we analyzed which combinations of backsheet-class inverters were connected to. Only a few inverters (27%) are connected to modules with only one backsheet class, whereas the majority (73%) are connected to modules with backsheets from several classes. We found that ground impedance values of inverters connected to modules with FC and PA class backsheets were particularly low. Conspicuously, inverters connected to at least one module with an FC class backsheet tripped notably more. In all cases, tripping frequency increased exponentially with time. We observed no tripping for inverters connected exclusively to modules with backsheets from the 'others' (15%) class. Sorting modules according to their backsheet class and constructing single-backsheet inverters would reduce the risk of inverter tripping for the investigated photovoltaic (PV) system by 44%.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Backsheet variety; ground impedance (GI); insulation resistance; inverters